Krishna's Neglected Responsibilties: Religious devotion and social critique in eighteenth-century North India - Williams, R (Cambridge University Press, 2015)
This article examines the literary strategies employed by a devotional poet who wrote about recent events in the eighteenth century, in order to shed light on contemporary notions of social responsibility. Taking the poetic treatment of Ahmad Shah Abdali's invasion of North India and the sacking of Vrindavan in 1757 as its primary focus, the article will discuss how political and theological understandings of lordship converged at a popular level, such that a deity could be called to account as a neglectful landlord as well as venerated in a bhakti context. It examines the redaction of tropes inherited from both vaisnava literature and late Mughal ethical thought, and considers the parallels between the Harikala Beli, a Braj Bhasha poem, and immediately contemporary developments in Urdu literature, particularly the shahr ashob genre. As such, it uses poetic responses to traumatic events as a guide to the interaction between multiple intellectual systems concerned with human and divine expectations and obligations.